Effect of high DHA and ARA fortification on non-enzymatic browning of infant formula powder - Hong-Xin Jia; Hai-An Liu; Mi-Ya Su (CyTA - Journal of Food, 2024)
To investigate the effect of adding high-dose docosahexaenoic acid (DHA) and arachidonic acid (ARA) on the stability of infant formula powders (IFs), IFs fortified with high-dose and low-dose DHA and ARA were compared and evaluated during storage at 37°C for six months. We specifically focused on the changes to IFs caking, amino acid content, and 5-hydroxymethylfurfural (HMF) content. We found that during the storage process, there was no significant change in the amino acids of IFs following supplementation with high- or low-doses of DHA and ARA. However, HMF and color difference (∆E) increased with the length of storage time. A comparison between the high-dose and low-dose groups revealed that the addition of high-dose DHA and ARA did not cause an additional increase in the HMF but exacerbated the caking of IFs. The addition of high-dose DHA and ARA did not exacerbate the non-enzymatic browning of IFs.